Environmental Efficiency and Legal Possibility of mineralized water dispose in the suprasalt sequence of the Verkhnekamskoe deposit - Kvitkin Stanislav Yu.; Trofimov Vladimir I.; Kovalskaya Vera V. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2017)
The production of potash fertilizers at PJSC Uralkali is accompanied by the formation of excess solutions/ brines, located on the sludge dump, where also comes water from salt brines and tailing piles, clay-salt slimes and atmospheric precipitation. After mechanical purification and reduction of the solutions/brines mineralization in the order of 5 million m3/year are emitted into surface waters. The studies carried out by Uralkali in 2000-2006 at the Verkhnekamskoe field, revealed an opportunity of underground disposal of mineralized brines/wastewater in the upper part of the salt-marl layer, directly overlapping the salt deposits and situated at depths not exceeding 300 m. Obtained results are confirmed by the state geological commission of the Federal Agency on Mineral Resources. The location of mineralized solutions in reservoir beds with an almost unlimited capacitive potential does not lead to the change in the hydrodynamic and hydrochemical regime of the underground hydrosphere and lessen the burden on the environment. To implement underground disposal of mineralized process brines/wastewater, it is necessary to amend the «Concerning Subsurface Resources» Federal Law. Proposals of Uralkali to amend the «Concerning Subsurface Resources » Federal Law are supported by the Federal Agency for Mineral Resources and Federal Service for Supervision of Natural Resources.
Keywords: Verkhnekamskoe salt deposit; production of potash fertilizers; excess solutions; wastewater; suprasalt sequence of rocks; underground collectors; «brine» horizon